The role of downward assets volatility in assessing the book-value distance to default. Issue 4 (10th May 2019) - Coccorese, Paolo; Santucci, Laura
Abstract : Purpose: The purpose of this paper is to test the different definitions of "book-value distance to default" (BVDD) to assess whether using downward assets volatility provides some advantage to the index performance or produces adverse impacts on its effectiveness. Design/methodology/approach: Our BVDD is a modification of the Merton's "distance to default" and relies on accounting data only. A survival analysis is conducted by estimating a Cox semiparametric hazard model where the BVDD is built as a function of a parameter θ, which indicates the percentage of upward assets volatility incorporated in its calculation so as to compare its success in predicting banks' distress over different levels of θ . The investigation is performed on panel data regarding 866 Italian banks over 21 years. Findings: Results show that while the "pure" downward assets volatility does not catch all the nuances of risk, a small portion of upward deviation allows to notably increase the probability of identifying a distressed bank beforehand. Originality/value: This study adds to the literature by providing two main contributions. First, it confirms that the BVDD is a reliable measure, being able to predict whether a bank is going to face distress. To the best of the authors' knowledge, this is the first attempt to appraise BVDD's accuracy as an index for banks' soundness through a rigorous econometric experiment. Second, some important insights regarding the Italian banking system may be inferred: larger well-capitalized banks seem to be less likely to fail, whereas credit institutions with higher loans-to-assets ratios are found to be riskier.